Barriers in care for children with life-threatening conditions: a qualitative interview study in the Netherlands. Issue 6 (28th June 2020) - Brouwer, Marije; Maeckelberghe, Els L M; van der Heide, Agnes; Hein, Irma; Verhagen, Eduard
Abstract : Objective: To identify barriers, as perceived by parents, to good care for children with life-threatening conditions. Design: In a nationwide qualitative study, we held in-depth interviews regarding end-of-life care with parents of children (aged 1 to 12 years) who were living with a life-threatening illness or who had died after a medical trajectory (a maximum of 5 years after the death of the child). Sampling was aimed at obtaining maximum variety for a number of factors. The interviews were transcribed and analysed. Setting: The Netherlands. Participants: 64 parents of 44 children. Results: Parents identified six categories of difficulties that create barriers in the care for children with a life-threatening condition. First, parents wished for more empathetic and open communication about the illness and prognosis. Second, organisational barriers create bureaucratic obstacles and a lack of continuity of care. Third, parents wished for more involvement in decision-making. Fourth, parents wished they had more support from the healthcare team on end-of-life decision-making. Fifth, parents experienced a lack of attention for the family during the illness and after the death of their child. Sixth, parents experienced an overemphasis on symptom-treatment and lack of attention for their child as a person. Conclusions: The barriers as perceived by parents focussed almost without exception on non-medical aspects: patient-doctor relationships; communication; decision-making, including end-of-life decision-making; and organisation. The perceived barriers indicate that care for children with a life-threatening condition focusses too much on symptoms and not enough on the human beings behind these symptoms.